(untitled) (Altre Modernità, 2013)
Despite being firmly attached to the ground, plants move, just like other organisms. Spores and seeds constitute the usual vehicle, however every journey made by this dispersive structure, even their simple fall under gravitational pull, is conditioned by the random nature of natural processes and does not necessary lead to success. This applies both to natural dissemination, be it mediated (by air, water, animals, etc.) or autonomous (passive fall, active expulsion), and, particularly in this day and age, when dispersion is in some way associated with Homo sapiens. In this last case, it is essential to make a distinction between wild and cultivated, remembering that the dead end of any crop is reached when, due to guided selection, the plant loses all capacity for autonomous life. The whole of human history is characterised by plant transfers (opportunist species) that were largely unplanned and in part outside human control, taking root in the natural environment thereby damaging and deteriorating biodiversity, human economics and health. These transfers increased with the discovery of America as a consequence of the contacts with the colonies established by Europe all over the world. The analysis of the success of international plant transfers, be they voluntary and involuntary, allows us to identify their causes, measure their development and build a general model from which to ascertain the chances offered to each new appearance for its future in foreign soil. Invasiveness indicates the “excess” of an alien presence and figures negatively as an increasingly pressing problem for the future of our planet.